METODE DAKWAH MAU’IDZOTUL HASANAH TERHADAP KESADARAN DIRI SANTRI DI ASRAMA AL-NUR MA’HAD AL-ZAYTUN - Dina Rohmatul Jannah; Sobirin; Meity Suryandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Self-awareness is a fundamental foundation in shaping the character of santri who are strong both spiritually and emotionally. In pesantren education, dakwah serves not only to convey religious teachings but also to develop personality. This study aims to describe the implementation of the mau’idzotul hasanah method in fostering self-awareness among santri at Al-Nur Dormitory, Ma’had Al-Zaytun, and to identify its supporting and inhibiting factors. The theoretical framework refers to Daniel Goleman’s (1996) concept of self-awareness, which includes emotional awareness, accurate self-assessment, and self-confidence. This research employed a descriptive qualitative approach using direct observation, in-depth interviews, and relevant documentation and literature studies. The findings reveal that Al-Nur Dormitory functions as an internal dakwah institution that not only emphasizes discipline but also provides spiritual and character development. The mau’idzotul hasanah approach gentle, reflective, and emotionally engaging was proven to help santri recognize emotions, assess themselves honestly, and build self-confidence. Supporting factors include the role modeling of supervisors, personalized emotional approaches, a structured dormitory system, psychological readiness, and literacy activities as well as public speaking training. Inhibiting factors involve the diversity of santri backgrounds, emotional unpreparedness, inappropriate communication styles, the influence of social media, and a lack of synergy between parents and the dormitory. Nevertheless, Al-Nur Dormitory has effectively carried out its role in developing santri’s personality and spirituality through the mau’idzotul hasanah method. Keywords: dakwah method, mau’idzotul hasanah, self-awareness, religious guidance.